Dynamics of packed swarms: time-displaced correlators of two dimensional incompressible flocks - Chen,L; Lee,CF; Maitra,A; Toner,J (Physical Review E: Statistical, Nonlinear, and Soft Matter Physics, 2024)
We analytically calculate the scaling exponents of a two-dimensional KPZ-like system: coherentlymoving incompressible polar active fluids. Using three different renormalization group approxima-tion schemes, we obtain values for the “roughness” exponent χ and anisotropy exponent ζ that areextremely near the known exact results. This implies our prediction for the previously completelyunknown dynamic exponent z is likely to be quantitatively accurate.